Postmenopausal Tuberculosis Endometritis - Kemal Güngördük; Volkan Ulker; Ahmet Sahbaz; Cemal Ark; Alı Ismet Tekırdag (Hindawi Limited, 2007)
Tuberculosis remains a global health problem, primarily in developing countries with inadequate health services. A significant portion of tuberculosis in these settings is extrapulmonary, including tuberculosis of the genitourinary tract. Patients with genital tuberculosis are usually young women detected during work up for infertility. After menopause, tuberculosis of the endometrium is a rare possibility probably because of the decreased vascularity of the tissues. We present a case of endometrial tuberculosis with postmenopausal vaginal bleeding.